Convergencia y polarización. El caso Peruano: 1961 - 1996 - Odar, Juan Carlos (Estudios de Economía, 2016)
According to Growth Theory, different economies converge to the same steadystateif saving rates, depreciation and population growth are controlled.Controlling for other variables, convergence will be conditional and not absolute.If the considered economies are regions of the same country, in long-run all ofthem should share the same steady-state. This paper evaluates if convergencein Peru is conditioned by geographic variables. Evidence suggests that, causedby geographical factors, Peruvian regions follow different dynamics and thatthere are at least two economic regimes that converge to different steady-states.